2000
DOI: 10.1016/s0735-1097(00)00693-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of metoprolol CR/XL to maintain sinus rhythm after conversion from persistent atrial fibrillation

Abstract: The results of this double-blind, placebo-controlled study in patients after cardioversion of persistent atrial fibrillation showed that metoprolol CR/XL was effective in preventing relapse into atrial fibrillation or flutter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
19

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(139 citation statements)
references
References 40 publications
4
116
0
19
Order By: Relevance
“…A study investigated the effect on rhythm control in persistent AF patients who underwent electrical defibrillation using metoprolol, a β 1 -blocker similar to bisoprolol. 21) The results revealed that administration of metoprolol was effective in preventing AF recurrence. There are two reports comparing the suppressive effect of a β-blocker with that of an antiarrhythmic drug in P-AF patients.…”
Section: Discussionmentioning
confidence: 97%
“…A study investigated the effect on rhythm control in persistent AF patients who underwent electrical defibrillation using metoprolol, a β 1 -blocker similar to bisoprolol. 21) The results revealed that administration of metoprolol was effective in preventing AF recurrence. There are two reports comparing the suppressive effect of a β-blocker with that of an antiarrhythmic drug in P-AF patients.…”
Section: Discussionmentioning
confidence: 97%
“…Donoszono również, że beta-adrenolityki ograniczają występowanie objawowych nawrotów AF [580,636,688], ale ta obserwacja może wynikać z korzystnego wpływu kontroli częstości rytmu komór, która powoduje, że AF częściej staje się bezobjawowe.…”
Section: Antyarytmiczne Działanie Leków Nieantyarytmicznychunclassified
“…248,249,687 Compared with placebo, beta-blockers are associated with a reduced risk of new-onset AF in patients with HFrEF and sinus rhythm. 23 Beta-blockers have also been reported to reduce symptomatic AF recurrences, 580,636,688 but this finding may be driven by the beneficial effect of rate control, which will render AF more often asymptomatic.…”
Section: Antiarrhythmic Effects Of Non-antiarrhythmic Drugsmentioning
confidence: 99%